2020
DOI: 10.2147/copd.s276429
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC00987 Ameliorates COPD by Regulating LPS-Induced Cell Apoptosis, Oxidative Stress, Inflammation and Autophagy Through Let-7b-5p/SIRT1 Axis</p>

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is the third cause of diseaserelated death and brings a heavy burden to human health. Long non-coding RNA (lncRNA) was revealed to participate in COPD pathogenesis. This study aims to establish the effects and regulatory mechanism of lncRNA long intergenic non-coding 00987 (LINC00987) in lipopolysaccharide (LPS)-induced apoptosis, oxidative stress, inflammation and autophagy in BEAS-2B cells. Methods: The expression levels of LINC00987 and let-7b-5p were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…For example, COPDA1 promotes the proliferation of smooth muscle cells through upregulating the expression of MS4A1 in COPD ( Zheng et al, 2019 ). LINC00987 modulates LPS-induced cell apoptosis, oxidative stress, inflammation and autophagy through sponging let-7b-5p in COPD ( Wang et al, 2020 , Chen, Chen, Liu, Dong, Ji, Hu, Zhang). MEG3 targets miR-218 thereby regulating cigarette smoke extract (CSE)-inhibited proliferation and CSE-induced apoptosis in COPD ( Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, COPDA1 promotes the proliferation of smooth muscle cells through upregulating the expression of MS4A1 in COPD ( Zheng et al, 2019 ). LINC00987 modulates LPS-induced cell apoptosis, oxidative stress, inflammation and autophagy through sponging let-7b-5p in COPD ( Wang et al, 2020 , Chen, Chen, Liu, Dong, Ji, Hu, Zhang). MEG3 targets miR-218 thereby regulating cigarette smoke extract (CSE)-inhibited proliferation and CSE-induced apoptosis in COPD ( Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…LINC00987 was transfected into LPS-induced 16HBE and BEAS-2B cells with a control group. LINC00987 protected 16HBE and BEAS-2B cells from LPS-induced apoptosis, oxidative stress, inflammation, and autophagy (Wang et al, 2020). In our research, LINC00987 upregulation was found to be deeply involved in immune system events.…”
Section: Discussionsupporting
confidence: 55%
“…Among the 14 lncRNAs in MylnBrna, several lncRNAs have been well studied in several abnormal metabolic diseases and tumours. For instance, ensg00000237248 (LINC00987) has been reported to ameliorate chronic obstructive pulmonary disease through modulating lipopolysaccharide-induced cell apoptosis, oxidative stress, inflammation, and autophagy via regulating other gene signalling pathways [ 39 ]. The down-regulation of ensg00000232352 (lncRNA SEMA3B-AS1) was related to risky outcomes of patients with Wilms tumour [ 40 ].…”
Section: Discussionmentioning
confidence: 99%